Source strength determination in iridium-192 and cobalt-60 brachytherapy: A European survey on the level of agreement between clinical measurements and manufacturer certificates. (July 2021) - Vijande, Javier; Carlsson Tedgren, Åsa; Ballester, Facundo; Baltas, Dimos; Papagiannis, Panagiotis; Rivard, Mark J.; Siebert, Frank-André; De Werd, Larry; Perez-Calatayud, Jose
Abstract: Background and purpose: Brachytherapy treatment outcomes depend on the accuracy of the delivered dose distribution, which is proportional to the reference air-kerma rate ( RAKR ). Current societal recommendations require the medical physicist to compare the measured RAKR values to the manufacturer source calibration certificate. The purpose of this work was to report agreement observed in current clinical practice in the European Union. Materials and methods: A European survey was performed for high- and pulsed-dose-rate (HDR and PDR) high-energy sources ( 192 Ir and 60 Co), to quantify observed RAKR differences. Medical physicists at eighteen hospitals from eight European countries were contacted, providing 1, 032 data points from 2001 to 2020. Results: Over the survey period, 77% of the 192 Ir measurements used a well chamber instead of the older Krieger phantom method. Mean differences with the manufacturer calibration certificate were 0.01% ± 1.15% for 192 Ir and –0.1% ± 1.3% for 60 Co. Over 95% of RAKR measurements in the clinic were within 3% of the manufacturer calibration certificate. Conclusions: This study showed that the agreement level was generally better than that reflected in prior societal recommendations positing 5%. Future recommendations on high-energy HDR and PDR source calibrations in the clinic may consider tightened agreements levels.